Psychometric properties of the short message service problem use diagnostic questionnaire among Iranian students - Zeinab Shayeghian; Kazem Rasoolzadeh Tabtabae; Atiye Sadat Motaghi Ghamsari (Gonabad University of Medical Sciences, 2015)
The Excessive use of short massage services can lead to traumatic psychological, interpersonal and social consequences. The aim of the present study was to evaluate the psychometric properties of the SMS Problem Use Diagnostic Questionnaire (SMS-PUDQ). The sample consisted of 200 students of Tehran University of medical sciences which were selected through convenience sampling. The participants responded to the SMS-PUDQ, the APS (MMPI-II) and the GHQ-28. The validity of the questionnaire was investigated by convergent and discriminative validity and exploratory factor analysis. Results from factor analysis of the SMS-PUDQ using Varimax rotation method, yielded 2 factors which explained 75.50% of the total variance. SMS-PUDQ inter-factor correlations were significant (p < 0.01). Convergent validity was assessed by computing a correlation coefficient between SMS-PUDQ, APS and GHQ-28 total scores, which was 0.75 and -0.42. Alpha Cronbach coefficient of internal consistency for total score SMS-PUDQ was 0.91 and 0.95 using a spilt-half method. In general, findings of this research confirm the validity and reliability of the Persian version of SMS-PUDQ and show that this questionnaire can be valid scale for using In Iranian population for Diagnosis of SMS problem use.